Social functioning using direct and indirect measures with children with High Functioning Autism, nonverbal learning disability, and typically developing children. Issue 3 (2nd April 2016) - Semrud-Clikeman, Margaret; Fine, Jodene Goldenring; Bledsoe, Jesse
Abstract : Social perception is an important underlying foundation for emotional development and overall adaptation. The majority of studies with children with High Functioning Autism (HFA) or nonverbal learning disabilities (NLD) evaluating social functioning have used measures of parent and/or teacher ratings. The present study utilized parent and teacher ratings of behavior as well as executive functioning in addition to direct measures of social perception. Three groups participated in this study (control [ n  = 38] HFA [ n  = 36], NLD [ n  = 31]). Results indicated that the HFA group experienced the most difficulty understanding emotional cues on the direct measure while both the HFA and NLD groups experienced difficulty with nonverbal cues. Significant difficulties were reported on the parent rating scale for sadness and social withdrawal for both clinical groups. Executive functioning was found to be particularly problematic for the clinical groups. The direct social perception measure was highly correlated with the measures of executive functioning and reflects the contribution that executive functions have on social functioning. These findings suggest that the clinical presentation on behavior rating scales may be very similar for children with HFA and NLD. Moreover, it appears that measures of executive functioning are sensitive to the clinical difficulties these groups experience. The findings also suggest there is a commonality in these disorders that warrants further investigation.